2014
DOI: 10.1007/s10532-014-9703-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polycyclic aromatic hydrocarbons on microbial community structure and PAH ring hydroxylating dioxygenase gene abundance in soil

Abstract: Development of successful bioremediation strategies for environments contaminated with recalcitrant pollutants requires in-depth knowledge of the microorganisms and microbial processes involved in degradation. The response of soil microbial communities to three polycyclic aromatic hydrocarbons, phenanthrene (3-ring), fluoranthene (4-ring) and benzo(a)pyrene (5-ring), was examined. Profiles of bacterial, archaeal and fungal communities were generated using molecular fingerprinting techniques (TRFLP, ARISA) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
39
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 52 publications
4
39
1
2
Order By: Relevance
“…4). High PAH concentrations can lead to substantial changes in microbial community structure and diversity as shown in previous studies (Sawulski et al 2014) but their effects were comparatively small in the current experiment. This might be attributed to a dilution effect in paddy fields when the sewage sludges were applied to relatively large areas of agricultural land and to the degradation of indigenous microorganisms in the soil.…”
Section: Discussionsupporting
confidence: 64%
“…4). High PAH concentrations can lead to substantial changes in microbial community structure and diversity as shown in previous studies (Sawulski et al 2014) but their effects were comparatively small in the current experiment. This might be attributed to a dilution effect in paddy fields when the sewage sludges were applied to relatively large areas of agricultural land and to the degradation of indigenous microorganisms in the soil.…”
Section: Discussionsupporting
confidence: 64%
“…Genes involved in degradation of PAHs, such as those encoding ring hydroxylating dioxygenases (RHD) serve as useful biomarkers for the presence of potential PAHdegrading bacteria in soil (Doyle et al 2008). Recently, Sawulski et al (2014) showed that soil microbial assemblages responded differently to phenanthrene, fluoranthene and benzo(a)pyrene when these PAHs were added to soil as single contaminants. However, soils contaminated with PAHs typically contain mixtures of compounds differing in structure, susceptibility to degradation and toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the response of indigenous soil bacterial and fungal communities to mixtures containing phenanthrene, fluoranthene and benzo(a)pyrene in various combinations was examined using molecular fingerprinting techniques and quantification of a key PAH degradative gene. Results were compared to a parallel study by Sawulski et al (2014) which examined the effect of these PAHs on soil microbial communities when added as single contaminants. The rate of degradation of individual PAHs varied depending on whether the PAH was present as a single contaminant or in a mixture; phenanthrene was degraded most rapidly when present as a sole contaminant, fluoranthene was removed faster in the presence of the lower molecular weight phenanthrene and the rate of benzo(a)pyrene degradation was reduced in the presence of the 4-ring PAH, fluoranthene.…”
mentioning
confidence: 99%
“…Given their final destination in carbon-rich forest soils, new exploration in the microbial response to low level PAHs exposure and degradation contributes to deeper understanding of their natural attenuation processes. Furthermore, the microbial diversity in forest soils, far away from the human activities and disturbance, is expected to be higher than the contaminated soils which were usually suppressed by the existence of toxic organic pollutants [20,22]. In the present study, DNA-SIP was applied to a China forest soil to study the PHE, ANT and FLT degradation and the organisms responsible for the degradation in this complex microbial biota.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, as a critical factor affecting the global fate of PAHs in mountain-forest organic-rich soil, microbial response to these pollutants is important and attractive, but remained yet-unknown. Besides, microbial diversities in forest soils are more dynamic and sensitive than those of contaminated soils due to their low historical exposure and less tolerance to toxic pollutants [20][21][22]. Forest soils are therefore hypothesized with unique PAHs degraders compared to those in contaminated soils and have the necessities to be investigated for unknown metabolic genes and pathways.…”
Section: Introductionmentioning
confidence: 99%